2021
DOI: 10.1063/5.0031337
|View full text |Cite
|
Sign up to set email alerts
|

Tuning spin–orbit coupling in (6,5) single-walled carbon nanotube doped with sp3 defects

Abstract: Single-walled carbon nanotubes (SWCNTs) containing sp3 defects are a promising class of optoelectronic materials with bright photoluminescence and demonstrated single-photon emission. Using density functional theory simulations, complemented by measurements, we investigate the electronic structure of a series of quantum defects attached to (6,5) SWCNT with the goal of tuning the spin–orbit coupling by introduction of a heavy atom in the defect structure. We characterize the ground state electronic and spin pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 100 publications
2
5
0
Order By: Relevance
“…Given the dimensions of the diazonium functional groups used in this study, the absence of signals from the 14,15 N, 17 O, and 35,37 Cl nuclei on the functional groups (about 0.5–0.7 nm away from the closest C on the SWCNTs) suggests that the electron spins are primarily confined at the defect sites on the SWCNT sidewalls rather than on the functional groups (Fig. 1a ), consistent with previous theoretical predictions 31 , 46 . This conclusion is also in agreement with the similar coherence times observed for the two types of SWCNTs.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Given the dimensions of the diazonium functional groups used in this study, the absence of signals from the 14,15 N, 17 O, and 35,37 Cl nuclei on the functional groups (about 0.5–0.7 nm away from the closest C on the SWCNTs) suggests that the electron spins are primarily confined at the defect sites on the SWCNT sidewalls rather than on the functional groups (Fig. 1a ), consistent with previous theoretical predictions 31 , 46 . This conclusion is also in agreement with the similar coherence times observed for the two types of SWCNTs.…”
Section: Resultssupporting
confidence: 90%
“…This system also offers the versatility to use different chemical motifs to introduce and tune magnetic interactions for sophisticated quantum architecture designs 1 , 50 . For example, the introduction of heavy metal ions in the vicinity of the defects may provide means for introducing spin anisotropy 46 . Representing a powerful combination of both top-down fabrication and bottom-up molecular approaches, defect-induced spins in SWCNTs are poised to serve as highly reproducible and integratable alternatives for spintronic and quantum devices.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the position of E 11 * matches well to E 11,T at a higher doping level, which makes it difficult to determine whether E 11 * in this data is a signature of a deep exciton trap, or due to trion formation because of functionalization with a charged species. The literature often discusses neutral aryl defects; , however, evidence for the existence of radical aryl defects giving rise to E 11 * has also been given. , It has also been shown that the defect formation is influenced by the condition under which functionalization takes place . A further discussion about the binding configuration and charging state would go beyond the scope of this paper.…”
Section: Resultsmentioning
confidence: 99%
“…The literature often discusses neutral aryl defects; 24,25 however, evidence for the existence of radical aryl defects giving rise to E 11 * has also been given. 57,58 It has also been shown that the defect formation is influenced by the condition under which functionalization takes place. 29 A further discussion about the binding configuration and charging state would go beyond the scope of this paper.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical control of surface modification in single-walled carbon nanotubes (SWCNTs) has recently taken a leap forward after the development of new synthetic routes for functionalization of SWCNTs with single-stranded DNA (ssDNA): wrapping, photochemistry utilizing singlet and triplet state pathways, , and well-established chemistries using diazonium salts, hypochlorite, and ozone functionalizations. In all of these cases, chemical functionalization creates a low-lying defect-associated E 11 * exciton state below the fundamental E 11 exciton band of the SWCNT that exhibits improved optical properties and is energetically tunable. ,, For example, in the case of ssDNA wrapping, it is hypothesized that the guanine nucleotide base uniquely reacts with the SWCNT surface to form a sp 3 or sp 2 hybridiztion defect with complete control over the spacing between the adjacent defects and hence their interdefect interactions and exciton delocalization properties. When utilizing photochemical routes, the photoexcited triplet pathway, in the absence of triplet-quenching oxygen species, has been shown to produce experimentally new atomistic configurations of defects expanding the diversity of bonding configurations on the SWCNT lattice.…”
mentioning
confidence: 99%